2017
DOI: 10.1016/j.oooo.2017.05.512
|View full text |Cite
|
Sign up to set email alerts
|

Chronic fibrosing osteomyelitis of the jaws: an important cause of recalcitrant facial pain. A clinicopathologic study of 331 cases in 227 patients

Abstract: On the basis of the findings of this study, CFOJ can be considered a unique entity with consistent clinicopathologic features. Its features suggest a pathogenesis based on bone marrow ischemia. CFOJ can be treated on a rational basis with a justifiable expectation of success and probable cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…A later study by the same group evaluated a new trans‐alveolar ultrasonic sonography device (TAU‐n) with better intraoral application (Lechner et al., 2020), which was reported to match the reliability of other methods such as CCL5 levels and cone beam imaging. The latter was evaluated in a subset of 20/227 patients, it was reported that NICO/FDOJ had only been identified in 80% of cases using cone beam imaging (Goldblatt et al., 2017). In a subset of 6/449 patients, agreement between cone beam imaging, histology and CCL5 levels was found to be inconsistent (Lechner et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A later study by the same group evaluated a new trans‐alveolar ultrasonic sonography device (TAU‐n) with better intraoral application (Lechner et al., 2020), which was reported to match the reliability of other methods such as CCL5 levels and cone beam imaging. The latter was evaluated in a subset of 20/227 patients, it was reported that NICO/FDOJ had only been identified in 80% of cases using cone beam imaging (Goldblatt et al., 2017). In a subset of 6/449 patients, agreement between cone beam imaging, histology and CCL5 levels was found to be inconsistent (Lechner et al., 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors suggest that NICO/FDOJ may also cause or aggravate other systemic diseases and that these cavitations in the jaw might be connected to rheumatic, neuralgic and chronic inflammatory diseases (Lechner & von Baehr, 2015a; Lechner et al., 2017). In the pathophysiological context, many more terms have been used over the years: for example, alveolar cavitational osteopathosis (Ratner et al., 1986), necrotizing ischaemic chronic osteitis (Brown, 1996), aseptic‐avascular osteonecrosis (Lechner et al., 2017), chronic fibrosing osteomyelitis of the jaws (Goldblatt et al., 2017), focal osteoporotic bone marrow defects and aseptic ischaemic osteonecrosis of jawbone (Lechner et al., 2020). In order to avoid confusion and to maintain comparability, the terms NICO or FDOJ will be used in this review and substituted for other terms as appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…The classical clinical features are pain, swelling, and erythema of the overlying tissues, fever, paresthesia of the inferior alveolar nerve, paresthesia of lower lip, adenopathy, trismus, malaise, fistulas, and sometimes pathologic fracture. [1][2][3][4][5][6][7] The pain is a generally deep and boring type. In the case of Acute osteomyelitis swelling and erythema is very common to see which indicates the cellulitic phase of the inflammatory process under the bone.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…[2][3][4][5] Staphylococcus aureus or Mycobacteria are the most specific bacteria causing infection, other causes may include trauma, radiation, or certain drugs. 6 Diminished host defense mechanism whether local or systemic contributes to its emergence. Diabetes, malignancies, autoimmune diseases, malnutrition are some of the other causes that may associate with osteomyelitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation